挑戰與應對——中國傳統哲學視角下ＡＩ時代的醫患關係: Challenges and Responses: The Physician - Patient Relationship in the AI Era - XU, Hanhui (International Journal of Chinese & Comparative Philosophy of Medicine, 2019)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. AI physicians may replace human physicians in the foreseeable future. This, according to some philosophers, would maximize patients’ autonomy by helping to eradicate the paternalistic model of the doctor–patient relationship. In my view, however, this trend might pose a new threat to patients’ autonomy: the domination of machines. AI physicians would become dominant, depriving patients of their autonomy. This issue cannot be appropriately addressed until an alternative view of the doctor–patient relationship is available. The Confucian perspective on this relationship may be helpful. In Confucian thought, interaction between the physician and the patient is crucial. Thus, a better model would involve doctors, patients and AI devices, with AI-based diagnosis helping doctors to serve patients as efficiently as possible. DOWNLOAD HISTORY | This article has been downloaded 22 times in Digital Commons before migrating into this platform.